Perancangan Pembangkit Listrik Pikohydro Dengan Tipe Turbin Screw - Ma'mun Abdul Karim; Jojo Sumarjo; Najmudin Fauji (Politeknik Negeri Padang, 2021)
The screw type water turbine is one type of water turbine that has the potential to generate electricity on a small scale that is environmentally friendly, where this screw type water turbine is very suitable for rivers and irrigation flows in the territory of Indonesia because the use or operation of this turbine only requires low turbine head, looking at the potential for irrigation river water flow with a discharge range of 0.01-0.1 m3/s located in the lowlands in a Karawang district, it is possible to install or apply this screw type water turbine. In this study aims to be able to utilize the source of irrigation flow so that it can be converted into a source of electrical energy that can be utilized by local residents and for lighting on roads that are still poorly lit. In the process of designing a screw type water turbine, mechanical calculations are carried out to determine thedimensions of the turbine blades, turbine shaft, transmission systems such as pulleys and belts, as well as the power that can be generated by the turbine, with a relative head between 0.5 meters, 0.75 meters, and 0.9 meters and determine the correct components. The results of this calculation are obtained in the form of output power from each different head height for head 0.5, the power obtained is 220.89795 watts, for the 0.75 m head, the power is 394.29519 watts, and for the height 0.9, the output power is 356.13926 watts, the results of the design will then be made and will be realized.